You are on page 1of 12

# GIKPKC7 94107 Parabola I Page 1

Introduction
10/8/98
Terms:
Normal Perpendicular to
Cartesian Equations involving x & y E.g. x2 = 4.a.y
Parametric Equations involving x & y but written in term of a third variable

## A parabola has a maximum value if a < 0

For any curve in the number plane:
 If, a.x2 + b.x + c = 0 on the x-axis
 If, a.x + b.x + c > 0
2
above the x-axis
 If, a.x2 + b.x + c < 0 below the x-axis

## Roots of Quadratic Equations:

 Roots = x-intercepts of a graph
 2 roots (negative and positive regions) of a parabola = Indefinite Function
 1 roots of a parabola = Not Called Anything
 No roots of a parabola and:
a > 0 it’s known as a Positive Definite
a < 0 it’s known as a Negative Definite

## Luke Cole Page 1

GIKPKC7 94107 Parabola I Page 2

The Discriminant:
 Under the square root sign of the quadratic formula = discriminant = 
Equation:  = b2 – 4.a.c

##  If,  < 0 no real roots

 If,  = 0 one real root (two equal roots)
 If,  > 0 two real roots (two unequal roots)
 If,  = perfect square = rational
 If,  = not a perfect square = irrational
 For, a.x2 + b.x + c > 0
<0 a>0
 For, 2
a.x + b.x + c < 0
<0 a<0

## Sum & Product of Roots:

General form: x2  ( + )x + . = 0
Proof:
If  and  are two roots of a quadratic equation then:
(x  )(x  ) = 0
 x2  ( + )x + . = 0 …

b
Equation:  
a
Sum of roots

c
Equation:  . 
a
Product of roots
Proof:
a.x2 + b.x + c = 0
b c
x 2  .x   0 …(2)
a a
Compare (2) to :
x2  ( + )x + . = 0
b c
x 2  .x   0
a a
b c
       &  . 
a a
b
  
a

## Luke Cole Page 2

GIKPKC7 94107 Parabola I Page 3

Equation: a1.x2 + b1.x + c1 = 0  a2.x2 + b2.x + c2 = 0
a1 = a2
b1 = b2
c1 = c2

## Equations Reducible to Quadratics:

2
E.g. Solve, x  3
x

A x2 + 2 = 3.x
(x – 2)(x – 1) = 0
x=2 & x=1

## E.g. Solve, 32.x – 4.3x + 3 = 0

A Let, u = 3x
 u2 – 4.u + 3 = 0
(u – 3)(u  1) = 0
u=3 & u=1
Sub, u = 3x into u = 3 & u = 1
3x = 3 & 3x = 1
x=1 & x=0

## Tangent’s and Normals:

 To find the gradient of a tangent use calculus (See: The Tangent & Derivative)
 To find the normal use the formula: m1.m2 =  1
E.g. Find the equation of the tangent and normal of y = x2 at (3, 9)
y = x2
dy
 2.x
dx
Sub x = 3 into 2.x to find tangent
m1 = 6
 Y – y = m1(X – x)
y – 9 = 6(x – 3)
 6.x – y – 9 = 0
Finding the Normal
 m1.m2 =  1
m2 =  1/6
 Y – y = m2(X – x)
y – 9 =  1/6(x – 3)
 x + 6.y – 57 = 0

## Luke Cole Page 3

GIKPKC7 94107 Parabola I Page 4

Parabola as a Locus
19/8/98
 The locus of a point that is equidistant from a fixed point and a fixed line is always
a parabola.

Definitions:
x2 = 4.a.y
Tangent
Focus Chord

(0, a)
Focal Length Focal Chord
a

(0, 0) Vertex
a
Directrix y=a

 When the Focal Chord is parallel to the Directrix it is called Latus rectum

Concave Up:
 The locus of point P(x, y) moving such that it is equidistant from (0, a) and the line
y =  a is a parabola
General Form: (x – h)2 = 4.a(y – k)
(h, k) = Vertex
a = Focal length
Proof: A[h, (k + a)]
P(x, y)
Since, PA = PB:
(x – h)2 + [y – (k + a)]2 =
(x – x)2 + [y  (k  a)]2
2
(x – h) = 4.a.y – 4.a.k
 (x – h)2 = 4.a(y – k) B[x, (k  a)] y=ka

## Luke Cole Page 4

GIKPKC7 94107 Parabola I Page 5

## The Alternative Case:

 The locus of point P(x, y) moving such that it is equidistant from (a, 0) and the line
x =  a is a parabola
General Form: (y – k)2 = 4.a(x – h)
Proof:

Since, PA = PB:
[x – (h + a)]2 + (y – k)2 = [x – (h – a)]2 + (y  y)2
(y – k)2 = 4.a.x – 4.a.h
 (y – k)2 = 4.a(x – h)
x=ha

A[(h + a), k]

## Parametric Equations of the Parabola:

Parametric of x2 = 4.a.y: x = 2.a.t & y = a.t2
t = Parametric
Proof:
x = 2.a.t …(1)
y = a.t2 …(2)
Sub (1) into (2):
2
 x 
y  a 
 2.a 
x2 = 4.a.y

## E.g. Find the cartesian equation of x = 3.t + 1 & y = 2.t – 3

x = 3.t + 1 …(1)
y = 2.t – 3 …(2)
Sub (1) into (2)
2 .x  2
y 3
3
2.x – 3.y – 11 = 0

## Luke Cole Page 5

GIKPKC7 94107 Parabola I Page 6

## Chords in Parametric Form:

If P(2.a.p, a.p2) and Q(2.a.q, a.q2) are any Two Points on the Parabola
x2 = 4.a.y Then
p q
Gradient: m PQ 
2
Proof:
a. p 2  a.q 2
m PQ 
2.a. p  2.a.q
a p  q  p  q 
=
2.a  p  q 
pq
 m PQ 
2

## The Equation of the Chord PQ Will Be

General Form: y  ½(p + q)x + a.p.q = 0
Proof:
Using the point, gradient formula:
 p q
y  a. p 2   a  2.a. p 
 2 
 y  ½(p + q)x + a.p.q = 0 …

## If PQ is a Focal Chord Then

General Form: p.q =  1
Proof:
x2 = 4.a.y has a focus (0, a) & the equation of PQ is y  ½(p + q)x + a.p.q = 0 then sub
(0, a) into the equation PQ:
a.p.q =  a
 p.q =  1

## Luke Cole Page 6

GIKPKC7 94107 Parabola I Page 7

## Tangents in Parametric Form:

The Tangent to the Parabola x2 = 4.a.y at P(2.a.p, a.p2) has
Equation: y – p.x + a.p2 = 0
Proof:
Differentiate x2 = 4.a.y to find gradient:
dy x

dx 2.a
2.a. p
=
2.a
 m=p …
Use the point, gradient formula to find equation:
y – a.p2 = p(x – 2.a.p)
 y – p.x + a.p2 = 0 …

The Tangents to the Parabola x2 = 4.a.y at the Points P(2.a.p, a.p2) and
Q(2.a.q, a.q2) Intersect at
Point: [a(p + q), a.p.q]
Proof:
Equation of the tangent a P is :
 y – p.x + a.p2 = 0 …(1)
Equation of the tangent a Q is the same as , but has ‘p’s as ‘q’s:
 y – q.x + a.q2 = 0 …(2)
Now, (1) – (2):
 p.x + q.x + a.p2  a.q2 = 0 P
(q – p)x + a(p  q)(p + q) = 0 Q
 x = a(p + q)
Sub x = a(p + q) into (1):
y – p[a(p + q)] + a.p2 = 0 Z
 y = a.p.q
 Z[a(p + q), apq] …

## Luke Cole Page 7

GIKPKC7 94107 Parabola I Page 8

## Normals in the Parametric Form:

The Normal to the Parabola x2 = 4.a.y at P(2.a.p, a.p2) has:
Equation: x + p.y = a.p3 + 2.a.p
1
p
Proof:
Use  and the perpendicular line formula:
m1.m =  1
p.m =  1
1
 m
p
Use the point, gradient formula to find the equation:
  1
y  a. p 2    x  2.a. p 
 p 
 x + p.y = a.p3 + 2.a.p …

The Normal’s to the Parabola x2 = 4.a.y at P(2.a.p, a.p2) and Q(2.a.q, a.q2)
Intersect at
Point: [ a.p.q(p + q), a(p2 + p.q + q2 + 2)]
Proof:
Equation of the tangent a P is :
 x + p.y = a.p3 + 2.a.p …(1)
Equation of the tangent a Q is the same as , but has ‘p’s as ‘q’s:
 x + q.y = a.q3 + 2.a.q …(2) Z
Now (1) – (2): Q
p.y – q.y – 2.a.p + 2.a.q – a.p3 + a.q3 = 0 P
 y = a(p2 + p.q + q2 + 2)
Sub y = a(p2 + pq + q2 + 2) into (1):
x + p[a(p2 + p.q + q2 + 2)] = a.p3 + 2.a.p
 x =  a.p.q(p + q)
 Z[ a.p.q(p + q), a(p2 + p.q + q2 + 2)]

## Luke Cole Page 8

GIKPKC7 94107 Parabola I Page 9

## Tangents in Cartesian Form:

The Equation of the Tangent to the Parabola x2 = 4.a.y at P(x1, y1) is
General Form: x.x1 = 2.a(y + y1)
Proof:
Differentiate x2 = 4ay to find gradient:
dy x

dx 2.a
x
 m 1 …
2.a
Use the point, gradient formula to find the equation:
x 
y  y 1   1  x  x1 
 2.a 
2.a(y – y1) = x1.x – x12
Since x2 = 4.a.y then, x12 = 4.a.y1:
2.a(y – y1) = x1.x – 4.a.y1
 x.x1 = 2.a(y + y1)

## Normal’s in Cartesian Form:

The Equation of the Normal at P(x1, y1) on the Parabola x2 = 4.a.y is
  2 .a 
General Form: y  y1    x  x 1 
 x1 
Proof:
Use  and the perpendicular formula:
 m1.m =  1
 x1 
  .m  1
 2.a 
 2.a
 m
x1
Use the point, gradient formula to find the equation:
  2.a 
 y  y1    x  x1 
 x1 

## Luke Cole Page 9

GIKPKC7 94107 Parabola I Page 10

## The Equation of the Chord of Contact XY of the Tangents

Drawn From the Point P(x1, y1) to the Parabola x2 = 4.a.y is:
General Form: x.x1 = 2.a(y + y1)
Proof:
The points in parametric form would be X(2.a.p, a.p2) and Y(2.a.q, a.q2); so the
equation of the chord is :
 y  ½(p + q)x + a.p.q = 0 X
The point were the tangents intersect is : Y
 P[a(p + q), a.p.q]
Now comparing the points P[a(p + q), a.p.q] & P(x1, y1):
x1 = a(p + q)
x
 pq  1 …(1)
a
y1 = a.p.q …(2)
Now sub (1) & (2) into : P
 x1 
y  ½.   .x + y1 = 0
a
 x.x1 = 2.a(y + y1)

## Luke Cole Page 10

GIKPKC7 94107 Parabola I Page 11

## Properties of a Parabola: x = 2at, y = at2

The Tangent to a Parabola at a Given Point is Equally Inclined
to the Axis and the Focal Chord Through the Point:
i.e. FPQ = PQF

## F = Focal chord = (0, a)

F P P = Point = (2.a.p, a.p2) Q =
Tangent x-intercept
FQP = 
QPF = 
Q Z

Proof:
Tangent at P is :
 y = p.x  a.p2
Let FQP = :
 tan (90  ) = p
cot  = p
1
 tan  
p
Also:
a. p 2  a
M FP 
2.a . p
p2  1
=
2. p
Using the angle between two lines formula:
p2  1
p
2. p
tan  
p2 1
1
2
1
tan  
p
 tan  = tan 
 FPQ = PQF

## Luke Cole Page 11

GIKPKC7 94107 Parabola I Page 12

## The Tangents at the Extremities of a Focal Chord Intersect at

Right Angles on the Directrix:
i.e. QZP = 90 & Lies on the Directrix
F = Focal Chord = (0, a)
Q = Tangent = (2.a.q, a.q2)
Q F P P = Tangent = (2.a.p, a.p2)
Directrix: y =  a

Proof:
Since PQ is a focal chord, p.q = 1; Tangent at P has gradient m1 = p; Tangent at Q
has gradient m2 = q:
p.q =  1
Use perpendicular general form:
 m1.m2 =  1
 Tangents are perpendicular
Tangents intersect at :
 [a(p + q), a.p.q]
So:
y = a.p.q …(1)
Sub p.q = 1 into (1):
y=a
This is the equation of the directrix
 Tangents intersect on the directrix